Metabolic host responses to infection by intracellular bacterial pathogens - Eisenreich, Wolfgang; Heesemann, Jürgen; Rudel, Thomas; Goebel, Werner (Frontiers in Cellular and Infection Microbiology, 2013)
The interaction of bacterial pathogens with mammalian hosts leads to a variety of physiological responses of the interacting partners aimed at an adaptation to the new situation. These responses include multiple metabolic changes in the affected host cells which are most obvious when the pathogen replicates within host cells as in case of intracellular bacterial pathogens. While the pathogen tries to deprive nutrients from the host cell, the host cell in return takes various metabolic countermeasures against the nutrient theft. During this conflicting interaction, the pathogen triggers metabolic host cell responses by means of common cell envelope components and specific virulence-associated factors. These host reactions generally promote replication of the pathogen. There is growing evidence that pathogen-specific factors may interfere in different ways with the complex regulatory network that controls the carbon and nitrogen metabolism of mammalian cells. The host cell defense answers include general metabolic reactions, like the generation of oxygen- and/or nitrogen-reactive species, and more specific measures aimed to prevent access to essential nutrients for the respective pathogen. Accurate results on metabolic host cell responses are often hampered by the use of cancer cell lines that already exhibit various de-regulated reactions in the primary carbon metabolism. Hence, there is an urgent need for cellular models that more closely reflect the in vivo infection conditions. The exact knowledge of the metabolic host cell responses may provide new interesting concepts for antibacterial therapies.